2015
DOI: 10.4102/curationis.v38i1.117
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the nut of service-learning in nursing at a higher educational institution

Abstract: BackgroundThe readiness of academics to engage in the service-learning (SL) institutionalisation process is not accentuated in research on SL institutionalisation in South Africa. The argument has been advanced that SL scholarship and willingness of key stakeholders are crucial for SL institutionalisation at the academic programme level.AimThe research focus of the study being reported here was on readiness of respondents to embed SL in the curricula of the nursing programme.MethodThis study used a quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This further indicates the need for SL to be formally embedded in the curriculum to ensure that teaching and training are in keeping with the national policy for higher education institutions and the University of Limpopo's policy on community engagement. Julie et al [13] reported similar findings at other higher education institutions in SA.…”
Section: Discussionsupporting
confidence: 52%
“…This further indicates the need for SL to be formally embedded in the curriculum to ensure that teaching and training are in keeping with the national policy for higher education institutions and the University of Limpopo's policy on community engagement. Julie et al [13] reported similar findings at other higher education institutions in SA.…”
Section: Discussionsupporting
confidence: 52%
“…The SoN at the UWC is part of the Community and Health Science Faculty. This SoN is the largest residential nursing school in South Africa and has offered the Bachelor of Nursing degree since 2004 according to Jeggels, Traut and Africa ( 2013 :2), as cited by Julie et al ( 2015 :4).…”
Section: Research Methods and Designmentioning
confidence: 99%
“…The five prescriptive elements for the SL implementation framework ( Figure 2 ) were formulated to bridge the gaps in the readiness for embedding SL in the undergraduate nursing programme, as identified by the core findings of Phases 1 and 2 (Julie 2014a :209). The key focal points aimed at (1) correcting the prevailing theory–practice gap that emanated from the conceptual confusion in the differentiation between SL and other forms of CE curricular activities (Julie 2014b :1832); (2) addressing the lack of knowledge relating to the national SL policy guidelines by involving academics; (3) capacity building and building SL scholarship in clinical supervisors (Julie et al 2015 :1); (4) developing an SL pedagogical model for the school by providing concrete implementation guidelines for embedding SL pedagogy in undergraduate nursing modules, and (5) formulating SL institutionalisation criteria for the nursing programme at the school in accordance with the SL quality indicators of the HEQC (Julie 2014a :211–218).…”
Section: Prescriptive Elements For the Service-learning Implementatiomentioning
confidence: 99%
See 1 more Smart Citation